Sveriges tillämpning av EU:s dataskyddsförordning är oförenlig med unionsrätten-Handlingsoffentlighet och frivilligt utgivningsbevis i förhållande till unionsrätten - Trana,Ludwig (2023)
The essay presents an examination of the Swedish constitutional provisions regarding public documents and voluntary release certificates in relation to the European Union's (EU) data protection regulation (2016/679). Within the framework of Swedish law, everyone has the right to access a public document with associated personal data. Furthermore, websites can be granted a voluntary publication certificate meaning that they escape the regulations of the data protection regulation. The Data Protection Regulation applies as law in Sweden and is applied to the processing of personal data. Articles 85 and 86 of the Data Protection Regulation provide for an opportunity for the Member State to combine the protection of personal data with freedom of expression and information. Sweden has implemented Article 85 and 86 of the Data Protection Regulation through the Data Protection Act (2018:218) 1:7, meaning that the public act and freedom of expression take precedence over the Data Protection Regulation. The function of the Swedish implementation is that Union law, both in terms of the EU's Charter of Fundamental Rights and the Data Protection Regulation, loses its legal effect. Such an implementation is not compatible with Union law to the extent that fundamental rights are undermined while Sweden does not comply with the principle of proportionality. The Swedish implementation is incompatible with EU law and contributes to the loss of fundamental rights.
Keywords: GDPR; Offentlighetsprincipen; Handlingsoffentlighet; Dataskyddsförordningen; Frivilligt utgivningsbevis; EU; Unionsrätten; Tryckfrihetsförordningen; Yttrandefrihetsgrundlagen; Europeiska unionen; allmän handling; Dataskyddsdirektivet; Dataskyddsrätt